Assessing the toxicity of polystyrene beads and silica particles on the microconsumer Brachionus calyciflorus at different timescales - Pawlak, Julia; Noetzel, Dominique C.; Drago, Claudia; Weithoff, Guntram (Frontiers in Environmental Science, 2022)
Environmental pollution by microplastics has become a severe problem in terrestrial and aquatic ecosystems and, according to actual prognoses, problems will further increase in the future. Therefore, it is of crucial importance to assess and quantify the risk for the biota. Standardized short-term toxicological procedures as well as methods quantifying potential toxic effects over the whole life span of an animal are required. We studied the effect of microplastics on a common freshwater invertebrate, the rotifer Brachionus calyciflorus at different time scales. We used pristine polystyrene spheres of 1, 3 and 6 µm diameter and fed them to the animals together with food algae in different ratios ranging from 0 to 50 % non-food particles. As a particle control, we used silica to distinguish between a pure particle effect and a plastic effect. After 24 hours, no toxic effect was found, neither with polystyrene nor with silica. After 96 hours a toxic effect was detectable for both particle types. The size of the particles played a negligible role. Studying the long-term effect by using life table experiments, we found a reduced reproduction when the animals were fed with 3 µm spheres together with similar-sized food algae. We conclude that the fitness reduction is mainly driven by the dilution of food by the non-food particles rather than by a direct toxic effect. To achieve these results a combination of short- and long-term experiments is necessary.